2017
DOI: 10.1038/jp.2016.268
|View full text |Cite
|
Sign up to set email alerts
|

Skin-to-skin contact after birth and the natural course of neurosteroid levels in healthy term newborns

Abstract: Objective:To determine the postnatal course of neurosteroid levels in relation to gender, mode of delivery and the extent of skin-to-skin (STS) contact during the first days of life in healthy term newborns.Study Design:Prospective observational study of 39 neonates in which parents recorded total duration of STS in the first 2 days and nine neurosteroids (dehydroepiandrosterone-sulfate, progesterone, pregnenolone, pregnenolone-sulfate, allopregnanolone, isopregnanolone, epipregnanolone, pregnanolone and pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The postnatal decline in progesterone, epipregnanolone and pregnanolone sulfate was more significant in infants born by VD compared to pre‐labour CS (McCallie et al . ). As this reaction is similar to that of foals with neonatal equine maladjustment syndrome, the authors suggest that this may be due to a lack of labour rather than the delivery mode itself.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…The postnatal decline in progesterone, epipregnanolone and pregnanolone sulfate was more significant in infants born by VD compared to pre‐labour CS (McCallie et al . ). As this reaction is similar to that of foals with neonatal equine maladjustment syndrome, the authors suggest that this may be due to a lack of labour rather than the delivery mode itself.…”
Section: Introductionmentioning
confidence: 97%
“…Skin to skin contact, resembling the Madigan squeeze technique, was administered to 39 full‐term neonates born via CS and VD during the first 2 days of life; a dose–response relationship was observed and a reduction in the levels of inhibitory neurosteroids (McCallie et al . ). Although this effect was only significant for pregnanolone in all deliveries, plus progesterone in infants delivered via VD, the authors suggested that a different response may be observed in critically ill or preterm infants (McCallie et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, there is evidence that SSC decreases infant neurosteroid levels, which may indicate decreased stress after birth and therefore better energy conservation and blood glucose stabilization. 24 Several studies have shown that SSC improves colostrum production and the likelihood of exclusive breastfeeding at hospital discharge. 25 , 26 Colostrum has been shown to stabilize newborn glucose levels as effectively as formula in the first few hours after birth.…”
Section: Discussionmentioning
confidence: 99%